Regional planning for target populations: A spatial interpretation of the redistribution with growth model - Tomlinson, Richard (Town and Regional Planning, 1983)
This article demonstrates how, in the context of developing countries, a regional development policy can incorporate the objectives of both regional growth and increased intra-regional equity. The mechanism for accommodating both objectives is highlighted by the linking features of the regional economy. As far as regional growth is concerned, the expected impact of the regional multiplier factor can be determined by analyzing the spatial characteristics of the liaison structure of the economic activities favored by regional policy. As far as this interregional equality is concerned, efforts can be made to predict the inter-regional distribution impact of regional policy by identifying which economic groups are connected to the relevant growth sector. The theoretical basis of the article is the Reversal of Growth Model of Development Economists - emphasizing that the policies that are followed must clearly identify specific needy groups. The analysis of shift impacts on growth and distribution during the three stages of the multiplication process, provides a mechanism for combining the goals of regional growth and equality, as well as identifying the mutual equations between them.